Pengaruh Substitusi Tepung Kulit Pisang Kepok dan Jenis Lemak terhadap Sifat Organoleptik Sponge Cake - Fatimah Az Zahra; Lucia Tri Pangesthi (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
Sponge cake is one of a cake from continental. The aim of this study is to understand: 1) The influence of substitution kepok banana peel flour toward the organoleptic sponge cake; 2) The influence of type of fat toward the organoleptic sponge cake; 3) The effect of interaction betwixt kapok banana peel flour substitutions and type of fat to the organoleptic sponge cake; 4) The best nutrition of sponge cake, including carbohydrates, protein, fat, water, and vitamin C.The research was an 3 level of substitution kepok banana peel flour 25%, 50%, 75%, and type of fat is margarine and butter. Retrieving data used of organoleptic test utilizing up to 35 panelists, comprising 10 trained panelists and 25 semi-trained ones. A double Anova and Duncan test are employed to analyze the data. Next, the greatest sponge cake in laboratories will be sought after in order to find the best organoleptic test findings.The result of this reseach was : 1) kepok banana peel flour substitions influenced (the colour, texture, flavor, pores, and taste); 2) Type of fat influenced ( the colour, texture, pores, and taste); 3) The interactions of kepok banana peel flour substitutions and type of fat did not influenced; 4) The nutrient of the best sponge cake was 54,56 g carbohydrates, 11,5 g protein, 3,18 fat, 28,85 g water, and 6,05 mg vitamin C.